Implementing the Inquiry Method in Teaching Maharah Qiroah for Mubtadi’ Level: Insights from Jean Piaget and Implications for Educational Management - Mustofa, Ahmad; Fattah Khoirun; M. Syukron Maksum; Afriana Santosa (Al-Qalam Institue, 2025)
This study aims to investigate the effectiveness of the inquiry method in teaching Maharah Qiro’ah for beginner-level (mubtadi’) students and to explore its implications for educational management in course institutions. The study employed a qualitative approach using a Classroom Action Research (CAR) design at Lembaga Insan Kamil Probolinggo. Primary data sources included students and teachers, collected through observations, interviews, and learning documentation. Data were analyzed using Miles and Huberman’s techniques, including data reduction, presentation, and verification. The findings indicate that implementing the inquiry method significantly enhances students’ Maharah Qiro’ah skills, promoting more fluent and accurate Arabic reading and deeper comprehension of the text. Moreover, the method fosters students’ critical and analytical thinking in line with their cognitive development stages. From an educational management perspective, the inquiry method encourages active learning environments, improves teaching effectiveness, and provides a structured approach for monitoring and evaluating student progress. Therefore, the inquiry method not only serves as an effective instructional strategy for Maharah Qiro’ah but also contributes to the improvement of educational quality and management practices in course institutions.